Vorticity Gramian of Compact Riemannian Manifolds - Omenyi, Louis; Nwaeze, Emmanuel; Oyakhire, Friday; Ekhator, Monday (Communications in Mathematics and Applications, 2022)
The vorticity of a vector field on 3-dimensional Euclidean space is usually given by the curl of the vector field. In this paper, we extend this concept to n-dimensional compact and oriented Riemannian manifold. We analyse many properties of this operation. We prove that a vector field on a compact Riemannian manifold admits a unique Helmholtz decomposition and establish that every smooth vector field on an open neighbourhood of a compact Riemannian manifold admits a Stokes’ type identity.